Pengaruh Gaya Kepemimpinan, Komunikasi, dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Restoran Kedai Kita Bogor - Firdayanti, Firdayanti; Ahmad, Juwaini; Ramly, Amir Tengku (Institut Pertanian Bogor, 2023)
The problem that is used as the object of research is that the leadership style applied to employees is still not good, there are communication barriers between superiors and employees that are still less effective and regulations regarding work discipline that must be obeyed by employees. This research was conducted with the aim of analyzing the factors that influence the performance of our restaurant kedai kita in Bogor. Data collection was through questionnaires and the data analysis technique used in this research was a quantitative method with the help of the SPSS 22.0 program. The assessment system used in this research is a Likert scale. This research uses multiple linear regression analysis. The population in this study was all restaurant employees, totaling 60 people. The sampling technique in this research used saturated sampling. The research results concluded that leadership style had a positive and significant effect on employee performance. Communication has a positive and significant effect on employee performance. Work discipline has a positive and significant effect on employee performance.